Penguindrum. 5 - Ikuhara, Kunihiko, 1964- (Seven Seas, 2021)
"THE TRUTH IS OUT THERE. To rescue Himari, whose days are numbered, Kanba has once again joined the mob! What will happen to those who chose different paths? At last, the "transfer of destiny" is complete. What will they do as the mysteries are slowly revealed? The finale arrives in Volume 5 of the manga adaptation!"--Back cover.